2018
DOI: 10.1080/13813455.2018.1443142
|View full text |Cite
|
Sign up to set email alerts
|

The effect of troxerutin on anxiety- and depressive-like behaviours in the offspring of high-fat diet fed dams

Abstract: This study aimed at investigating the metabolic and behavioural effects of troxerutin treatment in the offspring of high fat diet (HFD) fed dams. Female Wistar rats (n = 40) received normal diet (ND) or HFD for 8 weeks prior to breeding. After mating, pregnant animals were assigned to four subgroups: ND, ND + Tro (troxerutin 150 mg/kg/day), HFD, and HFD + Tro. On the 21st day, male offspring were weaned and fed ND until 12 weeks old. Behavioural tests were performed on postnatal day (PND) 80 and 90. Compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Depression‐like behavior has been evaluated with the Porsolt forced swim test. Multiple studies have shown that offspring of HFD dams spend less time in the open arms of the elevated plus maze compared to controls, consistent with increased anxiety 71‐77 . Anxiety‐like behavior in offspring of obese dams has also been noted in the morris water maze task, open field test, and light–dark transition tests 66,71,74 .…”
Section: Maternal Obesity and Neurodevelopmental And Psychiatric Morbidity In Offspringmentioning
confidence: 94%
See 1 more Smart Citation
“…Depression‐like behavior has been evaluated with the Porsolt forced swim test. Multiple studies have shown that offspring of HFD dams spend less time in the open arms of the elevated plus maze compared to controls, consistent with increased anxiety 71‐77 . Anxiety‐like behavior in offspring of obese dams has also been noted in the morris water maze task, open field test, and light–dark transition tests 66,71,74 .…”
Section: Maternal Obesity and Neurodevelopmental And Psychiatric Morbidity In Offspringmentioning
confidence: 94%
“…69 to controls, consistent with increased anxiety. [71][72][73][74][75][76][77] Anxiety-like behavior in offspring of obese dams has also been noted in the morris water maze task, open field test, and light-dark transition tests. 66,71,74. Depression-like behaviors have been observed in offspring exposed to maternal obesity and HFD on the forced swim test.…”
Section: Hyperactivitymentioning
confidence: 94%
“…Another in vivo study with mice treated with a high-fat diet indicated that chronic administration of TRX (150 mg/kg) during the pregnancy improved anxiety- and depressive-like behaviors probably via reducing the serum levels of cortisol, glucose and cholesterol. The results suggest that these effects of TRX may be related to its anti-inflammatory and anti-oxidant properties [ 111 ].…”
Section: Other Properties Of Interest Of Troxerutinmentioning
confidence: 99%
“…It was found that these neuroprotective effects of troxerutin are mediated by modulation of endothelial nitric oxide synthase (eNOS) coupling/decoupling status that not only enhanced nitric oxide (NO), but also diminished peroxynitrate level expression. Bayandor and colleagues examined the potential effect of troxerutin on anxiety-and depressive-like behaviors in the offspring of HFD fed dams [58]. HFD offspring demonstrated higher anxiety and depressive-like behaviors, higher blood sugar, cholesterol and cortisol levels compared to the control groups.…”
Section: Neuroprotective Effectmentioning
confidence: 99%